Remoção de etanol e benzeno em reator anaeróbio horizontal de leito fixo na presença de sulfato - Cattony, Eduardo Bosco Mattos; Ribeiro, Rogers; Zaiat, Marcelo; Foresti, Eugênio; Varesche, Maria Bernadete Amâncio [UNESP] (FapUNIFESP (SciELO), 2007)
In this study it is reported the operation of a horizontalflow anaerobic immobilized biomass (HAlB) reactor under sulfate-reducing condition which was also exposed to different amounts of ethanol and benzene. The HAIB reactor comprised of an immobilized biomass on polyurethane foam and ferrous and sodium sulfate solutions were used (91 and 550 mg.l -1, respectively), to promote a sulfate-reducing environment. Benzene was added at an initial concentration of 2.0 mg.l -1 followed by an increased to 9 e 10 mg. l -1, respectively. Ethanol was added at an initial concentration of 170 mg.l -1 followed by an increased range of 960 mg.l -1. The reactor was operated at 30 (± 2) °C with hydraulic detention time of 12 h. Organic matter removal efficiency of 90% with a maximum benzene degradation rate of 0.07 mv, benzene.mg -1 vss.d -1 Thus, this work corroborate the data obtained for Cattony et al (2005) and also demonstrate that compact units of HAIB reactors, under sulfate reducing conditions, are a potential alternative for in situ aromatic compounds bioremediation.
Ethanol and benzene removal in a horizontal-flow anaerobic immobilized biomass reactor in the presence of sulfate
Keywords: Anaerobic reactor; Benzene; Biofilm; Ethanol; Sulfate reduction and PCB/DGGE